Assessing the Impact of Urban Hydrological Processes on the Summertime Urban Climate in Nanjing Using the WRF Model. Issue 23 (8th December 2019) - Wang, Xueyuan; Miao, Shiguang; Liu, Hongnian; Sun, Jianning; Zhang, Ning; Zou, Jun
Abstract: The impacts of urban hydrological processes, such as anthropogenic latent heat (ALH), multilayer green roof systems (GRO), evaporation from impervious surfaces (EIMP), urban irrigation (IRR), and the urban "oasis effect" (OASIS) on regional hydrometeorology in Nanjing, are assessed by the Weather Research and Forecasting Single‐Layer Urban Canopy Models (WRF‐SLUCM). The results show that including all five urban hydrological processes, ALL best improves the prediction of near‐surface meteorology and has the largest correlation coefficients, the smallest root mean square errors, and the most accurate diurnal variations compared with observations. The improvements of ALH, GRO, and OASIS are larger than those of IRR and EIMP. The influence of ALH, GRO, and OASIS is comparable in commercial areas, whereas the influence of OASIS is significantly greater and plays essential roles in low‐intensity residential areas. Therefore, the overall effect of urban hydrological processes is especially large over low‐intensity residential areas, where the ALL case‐simulated monthly mean 2‐m air temperature (surface temperature) is reduced by approximately 1.3 (5.0) °C, the 2‐m specific humidity increases by 0.8 g kg –1, and the sensible heat (latent heat) flux is reduced (increased) at most by 90 W m –2 . The changes in the vertical profiles indicate that urban hydrological processes reduce the potential temperature and wind speed, whereas they increase specific humidity over the entire urban boundary layer, leading to a more stable atmospheric conditions, reduced vertical mixing, and weaker convective rolls. These effects could mitigate the intensity of urban heat/dry islands while simultaneously exacerbating low‐level air pollution. Key Points: Adding urban hydrological processes improves WRF model representation of the near‐surface meteorology and energy balance Urban hydrological processes cool and wet the entire urban PBL reduce wind speed and lead to more stable atmospheric conditions These effects of urban hydrological processes may mitigate urban heat/dry islands while simultaneously exacerbating low‐level pollution